Association between axillary lymph node involvement and clinicopathological features of breast cancer among Indonesian women (Medical Journal of Indonesia, 2020)
BACKGROUND Some clinicopathological features play roles in the spread of breast cancer to axillary lymph node (ALN). However, their roles as predictive factors are not well-established. This study was conducted to determine the correlation between the clinicopathological features of breast cancer and the risk of ALN involvement in Indonesian women. METHODS This cross-sectional study was conducted in Margono Soekarjo Hospital using archival data from January 2017 to June 2018. All subjects with breast cancer who had undergone modified radical mastectomies without any evidence of distant metastasis were included. Chi-square and Fisher’s exact tests were performed to assess the relationship between ALN involvement and age, menopausal status, laterality, tumor size, tumor stage, histological type, tumor grade, lymphovascular space invasion (LVSI), skin or nipple infiltration, perineural invasion, estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 status. The odds ratio of each variable was evaluated using ordinal regression analysis. RESULTS Stage 3 breast cancer had the worst status of ALN involvement compared with stage 1 (OR = 3.49; 95% CI = 1.51–8.08) and stage 2 (OR = 3.04; 95% CI = 1.32–6.98). Likewise, positive LVSI also had the worst status of ALN involvement compared with negative LVSI (OR = 8.68; 95% CI = 4.23–17.81). CONCLUSIONS Tumor stage and LVSI could be considered as independent predictive factors of ALN involvement in patients with breast cancer, especially among Indonesian women.